The Effect of Family-Based Iron Education on FE Tablet Consumption Compliance in Pregnant Women in the Era of the COVID-19 Pandemic at UPTD Puskesmas Palaran - Damaris Mangopang; Lukaman Nulhakim; Siti Raihanah (PT FORMOSA CENDEKIA GLOBAL, 2022)
Pregnant women who fail to take iron supplements can develop iron deficiency anemia which increases the risk of maternal bleeding. Family-based education can increase pregnant women's adherence to taking Fe tablets regularly. The purpose of this study was to determine the effect of family-based iron education on adherence to consumption of Fe tablets in pregnant women during the COVID-19 pandemic at the Palaran Health Center UPTD. The design of this study is a quasi-experimental pre-test and post-test control design. The total sample is 32 pregnant women taken by purposive sampling. The results of the Chi square statistical test for the level of adherence with a p value of 0.001 ≤ α = 0.05 and paired t-test and independent tests for differences and increased knowledge of pregnant women. It was concluded that there was an effect of family-based education on adherence to consumption of Fe tablets in pregnant women (p value 0.001).